2015
DOI: 10.1016/j.autneu.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Muscle mechanoreflex overactivity in hypertension: A role for centrally-derived nitric oxide

Abstract: The cardiovascular response to exercise is abnormally large in hypertension. Over the past decade, it has become clear that the exercise pressor reflex (a peripheral feed-back mechanism originating in skeletal muscle) contributes significantly to the generation of this hyper-responsiveness. Further, it has been determined that overactivity of the mechanically (muscle mechanoreflex) and chemically (muscle metaboreflex) sensitive components of the exercise pressor reflex underpin its dysfunction. Given the recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…At the molecular level, two important factors associated with the overactive exercise pressor reflex in hypertension are the lower nitric oxide (NO) bioavailability and the greater oxidative stress mediated by angiotensin II (Smith et al . ; Thomas, ). NO modulates neural signalling in the nucleus tractus solitarius and rostral ventrolateral medulla, two areas related to autonomic and cardiovascular regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the molecular level, two important factors associated with the overactive exercise pressor reflex in hypertension are the lower nitric oxide (NO) bioavailability and the greater oxidative stress mediated by angiotensin II (Smith et al . ; Thomas, ). NO modulates neural signalling in the nucleus tractus solitarius and rostral ventrolateral medulla, two areas related to autonomic and cardiovascular regulation.…”
Section: Discussionmentioning
confidence: 99%
“… a ; Smith et al . ), suggesting that NO bioavailability in the central nervous system may be decreased in hypertension. In this sense, oxidative enzymes activated by angiotensin II increase reactive oxygen species, such as superoxide anions.…”
Section: Discussionmentioning
confidence: 99%
“…Static (isometric) exercise causes heart rate-dependent increases in cardiac output accompanied by increased or unchanged peripheral vascular resistance resulting in substantially elevated BP [19,20]. There is emerging evidence that hypertension is associated with excessive pressor responses during muscle contraction; both mechanically (mechanoreflex) and metabolically (metaboreflex) driven components of the pressor reflex are suggested being involved [21,22]. Patients with hypertension were shown to produce exaggerated BP elevation and enhanced muscle sympathetic nerve activation during isometric handgrip exercise compared with age-related healthy controls [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…As another example, sensory information generated by stimulation of the EPR is processed within the medulla oblongata. Within the medulla, the production of nitric oxide (NO) within the nucleus tractus solitarius (NTS), the site most critical for processing EPR sensory signals, buffers reflex-induced increases in SNA (56). It has been demonstrated that expression of neuronal NO synthase (NOS), necessary for the production of NO, is reduced throughout a large portion of the NTS in hypertensive rats (47).…”
Section: Possible Central Mechanisms Mediating Muscle Reflex Improvemmentioning
confidence: 99%